1974
DOI: 10.1002/j.2050-0416.1974.tb03617.x
|View full text |Cite
|
Sign up to set email alerts
|

The ACTION OF ENDO-β-1,3-GLUCANASES ON BARLEY AND MALT Β-Glucans

Abstract: The jS-glucan extracted from ungerminated barley with water at 40°C has a much lower specific viscosity than the corresponding material isolated from a wort prepared at 65°C from a two-day germinated barley malt.Both glucans are similar in that they are polymers of /3-D-glucose, with approximately 74% of the linkages in the £-1,4 configuration and 26% in the £-1,3 configuration. However, the two glucans are not hydrolysed to the same extent either by a partially purified bacterial endo-)9-1,3-glucanase or by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…However, the level of enzyme activity produced during germination would seem excessive if the degradation of these deposits was the enzyme's sole function. It has also been reported that endo-l,3-13-glucanase has an effect on the mixed-linkage 13-glucans isolated from both barley and malt (7) and can cause the solubilization of insoluble mixed-linkage 13-glucans (2,22). As part of a project to study the regulation of the synthesis of these enzymes, the endo-1,3-13-glucanase enzyme was purified and sequenced.…”
Section: Introductionmentioning
confidence: 95%
“…However, the level of enzyme activity produced during germination would seem excessive if the degradation of these deposits was the enzyme's sole function. It has also been reported that endo-l,3-13-glucanase has an effect on the mixed-linkage 13-glucans isolated from both barley and malt (7) and can cause the solubilization of insoluble mixed-linkage 13-glucans (2,22). As part of a project to study the regulation of the synthesis of these enzymes, the endo-1,3-13-glucanase enzyme was purified and sequenced.…”
Section: Introductionmentioning
confidence: 95%
“…4 is hydrolyzed, the rate was 5 to 6 times less than D.P. 5 or 6, indicating an enzyme preference for longer sequences of (1)(2)(3)(4) (26) identified regions in Hordeum l-i-glucan that contained extended blocks of 4 to 10 (1-s) linkages, but did not identify regions containing more than a single (1--*3) linkage as proposed by earlier studies (2,4). It has been reported that Avena /3-Dglucan contains regions rich in (1-s4) and/or (1-*3) linkages (21 …”
Section: Resultsmentioning
confidence: 95%
“…Despite the pioneering studies on barley which date back to over a century, for example, in the 1900s 53 , in the 1920s 19 , in the 1950s 29,51 , in the 1960s 33 and studies by scientists of the 1970s to the present day 4,6,[12][13][14]18,[20][21][22][23]27,28,[30][31][32][35][36][37][38]40,41,44 , the complexity and incompleteness of our knowledge of grain physiology have resulted in continuous research on cereals, with research studies on barley and malt receiving the most attention when compared to other cereals. This is because of the pivotal role malted barley plays in many applications in the food, alcoholic and non-alcoholic beverage, baked products and the spirit industries.…”
Section: Effect Of Different Steeping Conditions On Endosperm Modificmentioning
confidence: 99%